The Critical Period of Infancy from a Developmental Psychology Perspective: A Literature Review - Rahma Fithri; Yuliana Intan Lestari (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
The infancy period (0-2 years) is a critical phase in human development characterized by rapid growth and development across multiple domains, including physical-motor, cognitive, language, social-emotional, moral, and religious aspects. This period is often referred to as part of the "golden age" because the child's brain develops very rapidly and the formation of personality foundations and basic abilities occurs fundamentally. This literature study aims to comprehensively analyze the various dimensions of child development during infancy from the perspective of developmental psychology, as well as to identify its implications for early childhood education and parenting. The method used is a qualitative approach through literature study by analyzing various relevant scientific sources. The results of the study indicate that development during infancy is holistic and interrelated across aspects, thus requiring appropriate, continuous stimulation based on an understanding of developmental psychology so that children's potential can develop optimally. The role of the family, especially parents, is a dominant factor in the success of children's growth and development in this phase.